PENGARUH KUALITAS LAYANAN DIGITAL TERHADAP KEPUASAN PASIEN BEROBAT PADA KLINIK DOKTER GIGI PAYAKUMBUH - Jum’adil Dwi Zulstra; Muthia Rahma Dianti; Masrizal; Hamidah Rahim (Smart Education, 2026)
This study aims to analyze the effect of E-Service Quality on patient satisfaction at Nofi Triani Dental Clinic, Payakumbuh. The study was motivated by a decline in patient visits from 2,616 visits in 2024 to 1,410 visits in 2025, indicating the need to evaluate the quality of services provided. A quantitative approach with a cross-sectional design was employed. The study population consisted of all patients receiving treatment at Nofi Triani Dental Clinic, while the sample was selected using an accidental sampling technique. The independent variable was E-Service Quality, which comprised the dimensions of Fulfillment, Responsiveness, Contact, System Availability, and Privacy, while patient satisfaction served as the dependent variable. Data were analyzed using binary logistic regression. The results revealed that E-Service Quality significantly influenced patient satisfaction. The Fulfillment dimension had a significant effect on patient satisfaction (p=0.038), Responsiveness had a significant effect and was identified as the most dominant factor (p=0.013; Exp(B)=1.395), and Contact also significantly affected patient satisfaction (p=0.046). Meanwhile, System Availability and Privacy did not show significant effects. The Nagelkerke R Square value of 0.217 indicates that E-Service Quality explains 21.7% of the variance in patient satisfaction, while the remaining 78.3% is influenced by other factors outside the research model. It can be concluded that improving service quality, particularly in terms of responsiveness, service fulfillment, and communication, can enhance patient satisfaction and support increased patient visits at Nofi Triani Dental Clinic, Payakumbuh.